New development: Are social impact bonds (SIBs) viable in Italy? A new roadmap. Issue 4 (6th June 2016) - Bengo, Irene; Calderini, Mario
Abstract : This paper presents a roadmap to support the development of social impact bonds (SIBs) in Italy. Current barriers and opportunities are explained. SIBs should be piloted in areas where the cultural, ideological, technical and governance barriers are low. Accurate measurement systems will be necessary and an effective governance structure needs to be agreed. With careful piloting and follow-up, the SIB model could be a solution to welfare and public service funding in Italy.